Amberlyst‐15 as a Green and Efficient Reusable Catalyst for Friedel‐Crafts Alkylation of Activated Arenes with N‐Sulfonyl Aldimines and Synthesis of Bis‐triarylmethanes. Issue 34 (13th September 2018) - Thirupathi, Ponnaboina; Venkatagiri, Noole; Reddy, Chepyala Krishna
Abstract: Amberlyst‐15 has been found to be an efficient and an inexpensive acidic heterogeneous catalyst for Friedel–Crafts alkylation of an activated arenes and N ‐sulfonyl aldimines at room temperature. A Friedel‐Crafts alkylation products further undergoes alkylation with another mole of activated arenes to afford bis‐triarylmethanes in single transformation. Non‐toxicity and high stability of catalyst, broad applicability to various substrates with good to high yields and a simple operational procedure are the major advantages of the present method. The catalyst can be easily recycled by simple filtration and reused consecutively four times times without significant loss of activity. Abstract : Amberlyst‐15 has been found to be an efficient and an inexpensive acidic heterogeneous catalyst for Friedel–Crafts alkylation of an activated arenes and N ‐sulfonyl aldimines at room temperature.